XML in Office 2003: Information Sharing with Desktop XML - Goldfarb, Charles; Walmsley, Priscilla (Charles F. Goldfarb definitive XML series., 2003)
Co-authors are the world-renowned inventor of markup languages and a developer of the W3C XML Schema specification Detailed coverage of Office 2003 Professional XML features, plus all the XML knowledge you need to use them Learn to edit your XML document with Word, analyze its data with Excel, store it with Access, and publish it to the Web with FrontPage® Build dynamic custom XML forms with the remarkable new InfoPath™ 2003-structured data collection with word processing flexibility From the Foreword by Jean Paoli, Microsoft XML Architect and co-editor of the W3C XML specification: "XML enabled the transfer of information from server to server and server to client, even in cross-platform environments. But the desktop, where documents are created and analyzed by millions of information workers, could not easily participate. Business-critical information was locked inside data storage systems or individual documents, forcing companies to adopt inefficient and duplicative business processes. "This is a book on re-inventing the way millions of people write and interact with documents. It succeeds in communicating the novel underlying vision of Office 2003 XML while focusing on task-oriented, hands-on skills for using the product." Desktop XML affects every Office 2003 Professional Edition user! It transforms millions of desktop computers from mere word processors into rich clients for Web services, editing front-ends for XML content management systems, and portals for XML-based application integration. And this book shows you how to benefit from it. You'll learn exactly what XML can do for you, and you'll master its key concepts, all in the context of the Office products you already know and use. With 200 tested and working code and markup examples and over 150 screenshots and illustrations from the actual shipped product (not betas), you'll see step by step how: Office users can share documents more easily, without error-prone rework, re-keying, or cut-and-paste. Office data from your documents can be captured for enterprise databases. Office documents can be kept up-to-date with live data from Web Services and enterprise data stores. Office solutions can overcome traditional limitations by using XML and Smart Documents. BONUS XML SKILLS SECTION! All the XML expertise you'll need, adapted for Office 2003 users from the best-selling Charles F. Goldfarb's XML Handbook, Fifth Edition : the XML language, XML Schema, XPath, XSLT, Web services ... and m...